1998
DOI: 10.1063/1.475508
|View full text |Cite
|
Sign up to set email alerts
|

Effect of guest–host interaction on Raman spectrum of a CO2 clathrate hydrate single crystal

Abstract: The polarized Raman spectra of an artificial CO2 clathrate hydrate single crystal have been measured in order to examine the crystal-orientation dependence of the Raman spectra. Since the crystal had crystallographic facets, the orientation of the crystal was determined by using the Miller indices of the facets. When the angle θ between the polarization plane of the incident laser beam and the direction of one of the 〈110〉 axes of the single crystal varied, it was observed that the intensities of the peaks, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
41
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 26 publications
1
41
1
Order By: Relevance
“…Taylor and Francis shall not be liable for any losses, actions, claims, proceedings, demands, costs, expenses, damages, and other liabilities whatsoever or howsoever caused arising directly or indirectly in connection with, in relation to or arising out of the use of the Content. In a system consisting of liquid water and a guest fluid that is sparingly soluble in water, it is generally accepted that an interface between the guest fluid and the liquid water is the preferential nucleation site for hydrates [1][2][3][4][5][6][7][8]. In addition, recent studies [1][2][3][4][5][6][7][8][9][10] have revealed that hydrate crystals grow into liquid water, if the liquid water has dissolved the guest substance up to saturation prior to hydrate formation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Taylor and Francis shall not be liable for any losses, actions, claims, proceedings, demands, costs, expenses, damages, and other liabilities whatsoever or howsoever caused arising directly or indirectly in connection with, in relation to or arising out of the use of the Content. In a system consisting of liquid water and a guest fluid that is sparingly soluble in water, it is generally accepted that an interface between the guest fluid and the liquid water is the preferential nucleation site for hydrates [1][2][3][4][5][6][7][8]. In addition, recent studies [1][2][3][4][5][6][7][8][9][10] have revealed that hydrate crystals grow into liquid water, if the liquid water has dissolved the guest substance up to saturation prior to hydrate formation.…”
mentioning
confidence: 99%
“…In a system consisting of liquid water and a guest fluid that is sparingly soluble in water, it is generally accepted that an interface between the guest fluid and the liquid water is the preferential nucleation site for hydrates [1][2][3][4][5][6][7][8]. In addition, recent studies [1][2][3][4][5][6][7][8][9][10] have revealed that hydrate crystals grow into liquid water, if the liquid water has dissolved the guest substance up to saturation prior to hydrate formation. Visual information available for hydrate formation, growth, and ageing in fourphase systems, consisting of guest substance þ hydrate þ liquid water þ sediments, is limited to the observations of Tohidi et al [9,10], whereas studies of simple threephase systems consisting of guest substance þ hydrate þ liquid water are abundant [1][2][3][4][5][6][7][8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The vibrational motion of N 2 in ice lattice is expected to govern the diffusion mechanism. The vibrational motion of linear molecules such as N 2 distorts the structure of ice lattice [12,13]. Using neutron scattering, Ikeda et al [14][15][16] confirmed that the rotational and translational motions of the linear molecule have strong influence on the dynamics of the surrounding hydrogen-bonded network.…”
Section: Introductionmentioning
confidence: 98%
“…The close Raman shift in both states suggests that the reorganization of H 2 O molecules around the CO 2 molecule is quite similar, signifying the existence of clathrate-like structures in the liquid state. [15,16] When salts are present in the solution, the high affinity between water molecules and the electrolytes promotes two processes that drive a decrease in the clathrate equilibrium temperature: (1) the reduction in the gas solubility and (2) the difficulty of the reorganization of the H 2 O molecules in the clathrate cage; salts do not take part of the solid structure. This is the so-called ''salting-out'' effect that we monitored by Raman spectroscopy.…”
mentioning
confidence: 99%